1999
DOI: 10.1002/met.19996103
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting of thunderstorms in the pre‐monsoon season at Delhi

Abstract: Accurate prediction of thunderstorms during the pre-monsoon season (April-June)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The discriminant analysis led to classify few selected, morning and afternoon thunderstorms with 53.33 and 42.20% accuracy and 20 variables. In the present study, more than 90% accurate forecasts are observed for thunderstorms with lead time 12 to 6 h. Ravi et al (2006) applied a multiple regression method to give a potential forecast in probabilistic terms using nine predictors for pre‐monsoon thunderstorms over Delhi, India. This was a potential method for operational use.…”
Section: Applicability and Limitationsmentioning
confidence: 66%
“…The discriminant analysis led to classify few selected, morning and afternoon thunderstorms with 53.33 and 42.20% accuracy and 20 variables. In the present study, more than 90% accurate forecasts are observed for thunderstorms with lead time 12 to 6 h. Ravi et al (2006) applied a multiple regression method to give a potential forecast in probabilistic terms using nine predictors for pre‐monsoon thunderstorms over Delhi, India. This was a potential method for operational use.…”
Section: Applicability and Limitationsmentioning
confidence: 66%
“…Thunderstorm study was mainly carried out using techniques/observations such as radars (Leslie et al 1977;Sen et al 2010;Srivastava et al 2010;Litta et al 2012), radiosonde (Ravi et al 1999;Basu and Mondal 2002;Chaudhari et al 2010;Tajbakhsh et al 2012;Pucik et al 2015), lightning network (Dieter 2014), electric field mill (Pawar and Kamra 2009;Pawar et al 2014) and numerical models like WRF (Litta and Mohanty 2008;Litta et al 2012 and references there within), where the extrapolation of radar reflectivity echoes to forecast the location of convective storms was used widely. But the accuracy of these forecasts generally decreases rapidly during the first 30 min because of the very short lifetime of individual convective storms.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, south‐west monsoon (June to September) cloud systems over the same region are relatively widespread and have three to four times lower cloud base, with less tall clouds as compared with the pre‐monsoon season (Chaudhuri, ). Over Northwest Indian plain regions, these systems are less organized, mesoscale in temporal and spatial extent and often accompanied by hail during the pre‐monsoon season (Ravi et al ., ).…”
Section: Introductionmentioning
confidence: 99%